ANALYSIS OF JUNIOR HIGH SCHOOL STUDENTS LEVEL ON SCIENCE PROCESS SKILLS - Tuti Lestari; Dewi, Sepni Linda (SEMESTA: Journal of Science Education and Teaching, 2024)
Science process skills are students’ ability to understand learning not only limited to concepts but also the ability to solve the problems by collecting fact through scientific discoveries.This research aims to analyze  the mastery of science process skills of VII students at SMPN 7 Padang on life organization material. This research is quantitative descriptive research. The population of the research are the classes in seventh grade in SMPN 7 Padang. In this study the researcher limited the sample to two classes from a total eight classes with a total of 57 students. Data collection was carried out using two instruments, namely a performance assessment sheet and a written test in the form of multiple choice questions. The research result shows that the mastery of science process skills is in the sufficient category with an average score based on the indicators studied was 55,9%.